English teachers oft-cited barriers and strategies to overcome the barriers in online assessment: the case of senior and vocational high schools in Indonesia - Nanda Pambudi; Dyah Setyowati Ciptaningrum (Journal on English as a Foreign Language, 2023)
Copious studies on online assessment have been documented. However, little is known about English teachers oft-cited barriers in online assessment and their strategies to overcome the barriers. The present study aims to examine the oft-cited barriers by English teachers in online assessment during the COVID-19 pandemic and describe how they overcome the barriers. The study applied quantitative and qualitative methods in a sequential explanatory research design. Through a random sampling technique, it involved 96 senior and 28 vocational high school English teachers in Kampar, Riau, Indonesia. The quantitative data were gathered through closed-ended questionnaires and analyzed using descriptive statistics in SPSS 25, while the qualitative data were gathered using semi-structured interviews and analyzed using thematic analysis. The results revealed that English teachers face technological barriers as the main barriers in online assessment rather than pedagogical, institutional, and affective barriers. English teachers overcome the barriers by changing the form of assignments, especially in English assignments, to written form rather than other forms. The findings suggest important practical implications in the English classes for teachers and institutions to facilitate the teachers' and schools' needs in online assessment to enhance accessibility and quality during the pandemic.